2021
DOI: 10.7717/peerj.11758
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and suicidal ideation in Chinese children and adolescents: the mediation of resilience

Abstract: Background Childhood maltreatment could increase the risk of suicidal ideation (SI) in adolescents. However, the mediation of resilience in this association remains unclear. Methods A population-based cross-sectional study has been done among 3,146 Chinese adolescents. We collected relevant information from the study participants by using self-administered questionnaire. Chinese version of the Childhood Trauma Questionnaire (CTQ), the Resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…We found that psychological resilience mediated the association between childhood abuse and suicidal ideation, which corroborates previous findings (Chen et al, 2021 ). For instance, a survey found that resilience partially mediated the effect of childhood maltreatment on self-harm behaviours among adolescents (Tian et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that psychological resilience mediated the association between childhood abuse and suicidal ideation, which corroborates previous findings (Chen et al, 2021 ). For instance, a survey found that resilience partially mediated the effect of childhood maltreatment on self-harm behaviours among adolescents (Tian et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…As noted by Roy et al ( 2011 ), psychological resilience prevented individuals who were exposed to childhood traumas from suicide attempts. Further, a study among Chinese adolescents revealed that resilience partially mediated the effect of childhood maltreatment on suicidal ideation (Chen et al, 2021 ). Therefore, we hypothesized that psychological resilience mediated the relationship between childhood abuse and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adolescents who had not experienced CM, victims are seen statistically higher odds of SI. This finding was in agreement with two previous largescale population-based longitudinal studies [9,10]. The connection between CM and suicidality has been repeatedly validated.…”
Section: Discussionsupporting
confidence: 92%
“…CM imposes serious and profound psychological impairment to the victims: compared to non-abused counterparts, children and adolescents who had experienced CM showed higher level of generalized guilt, shame, depression, and anxiety [7,8]. CM also relates to increased risk of SI: findings from the National Comorbidity Survey Replication (NCS-R) suggested that CM was associated with an increased odds of SI (OR = 1.80) in 5665 US adults [9]; in another newly published cross-sectional study of 3146 Chinese children and adolescents, study subjects who had ever experienced any type of CM were 1.74 times more likely to report SI [10].…”
Section: Introductionmentioning
confidence: 99%
“…With the observation of the fact that a number of individuals exposed to high suicide risks would not be suicidal, researchers in the suicide field have become more and more interested in the phenomenon of resilience ( 9 ). Empirical findings have indicated that resilience represents an intermediate between suicide risk factors and suicidality, and may mitigate the adverse effect of suicide risk factors ( 10 , 11 ). Furthermore, individuals with low resilience were associated with an increased risk of lifelong suicidal behaviors ( 12 ).…”
Section: Introductionmentioning
confidence: 99%